PROBLEMATIKA GURU PADA PEMBELAJARAN BAHASA ARAB DI KELAS VI MADRASAH IBTIDAIYAH NEGERI 10 BANJAR - M. Ilmi M. Ilmi; Nadiyah - Nadiyah (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
This study discusses the problems of teachers in learning Arabic in class VI Madrasah Ibtidaiyah Negeri 10 Banjar. The formulation of the problem in this study is how the teacher's problematics in learning Arabic in class VI Madrasah Ibtidaiyah Negeri 10 Banjar and what factors influence it. Subjects in this study were Arabic language teachers and 58th grade VI students. While the object in this study is the problematic of teachers in learning Arabic in class VI Madrasah Ibtidaiyah Negeri 10 Banjar and what factors influence it. This type of research is descriptive field research, while the approach used in this study is qualitative research. For data mining, researchers used interviews, observation, questionnaire and documentary techniques. Based on the results of the study, it is known that the problematic of teachers in learning Arabic in class VI Madrasah Ibtidaiyah Negeri 10 Banjar is a problem related to curriculum material because the material is too much and difficult to understand by students and because of the limited allocation of time available and problems related to teaching methods are caused because it is difficult for teachers to apply the methods commonly used for learning Arabic at the ibtidaiyah level and the factors that influence teacher problems in learning Arabic in class VI Madrasah Ibtidaiyah Negeri 10 Banjar are student factors, teacher factors, facility factors, and factors Time Allocation. Keywords: Teacher Problems, Arabic Learning, Madrasah Ibtidaiyah.